The Role Of Nutritional Support In Critically Ill Patients: New Data And Recommendations (Literature Review). - Toshev Izzat Ikromovich (Genius Journals, 2025)
In recent decades, nutritional support has become key in the complex therapy of critically ill patients, significantly affecting the outcome of the disease, the course of organ dysfunction, and overall survival. Critical conditions are characterized by severe hypermetabolism , catabolic metabolism, immune dysfunction, and the risk of developing nutritional deficiency already on the first day of stay in the intensive care unit (ICU). Current recommendations emphasize the early initiation of enteral nutrition, preferably within 24–48 hours after stabilization of hemodynamic parameters, which helps maintain the intestinal barrier function, reduce bacterial translocation , and reduce the risk of infectious complications and multiple organ failure. In this article, we will consider the role of nutritional support in the ICU in seriously ill patients
Keywords: nutritional support; metabolism; barrier functions